Long-lasting remission in a metastatic hepatocellular carcinoma patient after combined regorafenib therapy and surgery - Elisabetta Goio; Luca Ielasi; Francesca Benevento; Matteo Renzulli; Francesco Tovoli (Hepatic Oncology)
Aims: The therapeutic scenario of systemic treatments for hepatocellular carcinoma (HCC) is rapidly changing. There is much interest in the possibility of combining new therapies with surgery, but clinical data is lacking. We aimed to provide an example of such integration. Patients & methods: We report a patient with metastatic HCC who received regorafenib in the setting of the RESORCE trial. Results: A brilliant response led to a tumor downstaging and a subsequent adrenal metastasectomy with radical intent. Conclusions: New agents will change the therapeutic perspectives in advanced HCC and lead to a higher rate of objective responses, with possibilities of associating systemic therapy and surgery. Thus, the management of HCC will require more and more of an integrated, multidisciplinary and personalized approach.